The psychological contracts of violation victims: A post‐violation model. (6th March 2015) - Tomprou, Maria; Rousseau, Denise M.; Hansen, Samantha D.
Summary: Organizations may fail to keep their commitments to their employees, at times leading to psychological contract violation. Although many victims of violation remain with their employer despite such adverse experiences, little research exists on their responses in the aftermath of violation. This paper develops a post‐violation model to explain systematically how violation victims respond to and cope with violation and the effects this process has on their subsequent psychological contract. Central to post‐violation are the victims' beliefs regarding the likelihood of violation resolution and the factors affecting it. The model specifies how the victim engages in a self‐regulation process that results in an array of potential psychological contract outcomes. Possible outcomes include reactivation of the original pre‐violation contract, the formation of a new contract that may be more or less attractive than the original, or a state of dissolution wherein the victim fails to form a functional psychological contract with the employer. The research and practical implications of this model are discussed. Copyright © 2015 John Wiley & Sons, Ltd.